Whole lung lavage therapy for pulmonary alveolar proteinosis: a global survey of current practices and procedures. Issue 1 (December 2016) - Campo, Ilaria; Luisetti, Maurizio; Griese, Matthias; Trapnell, Bruce; Bonella, Francesco; Grutters, Jan; Nakata, Koh; Van Moorsel, Coline; Costabel, Ulrich; Cottin, Vincent; Ichiwata, Toshio; Inoue, Yoshikazu; et al.
Abstract Background Whole lung lavage (WLL) is the current standard of care treatment for patients affected by pulmonary alveolar proteinosis (PAP). However, WLL is not standardized and international consensus documents are lacking. Our aim was to obtain a factual portrayal of WLL as currently practiced with respect to the procedure, indications for its use, evaluation of therapeutic benefit and complication rate. Methods A clinical practice survey was conducted globally by means of a questionnaire and included 27 centers performing WLL in pediatric and/or adult PAP patients. Results We collected completed questionnaires from 20 centres in 14 countries, practicing WLL in adults and 10 centers in 6 countries, practicing WLL in pediatric patients. WLL is almost universally performed under general anesthesia, with a double-lumen endobronchial tube in two consecutive sessions, with an interval of 1–2 weeks between sessions in approximately 50 % of centres. The use of saline warmed to 37 °C, drainage of lung lavage fluid by gravity and indications for WLL therapy in PAP were homogenous across centres. There was great variation in the choice of the first lung to be lavaged: 50 % of centres based the choice on imaging, whereas 50 % always started with the left lung. The choice of position was also widely discordant; the supine position was chosen by 50 % of centres. Other aspects varied significantly among centres including contraindications, methods and timing of follow up, use of chest percussion, timing of extubation following WLL and lung isolation and lavage methods for small children. The amount of fluid used to perform the WLL is a critical aspect. Whilst a general consensus exists on the single aliquot of fluid for lavage (around 800 ml of warm saline, in adults) great variability exists in the total volume instilled per lung, ranging from 5 to 40 liters, with an average of 15.4 liters/lung. Conclusions This international survey found that WLL is safe and effective as therapy for PAP. However these results also indicate that standardization of the procedure is required; the present survey represents the a first step toward building such a document.